THE INFLUENCE OF TRAINING AND DEVELOPMENT, WORK MOTIVATION AND TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE THROUGH COMPETENCY AS AN INTERVENING VARIABLE - Lumbantobing, Dominicus Doli Senjaya; Nadlifatin, Reny (Universitas Nahdlatul Ulama Surabaya, 2025)
A company must establish core values to enhance employee competency, a crucial element for organizational progress. In the face of increasingly competitive global markets, improving employee competency is vital for fostering innovation, creativity, and the swift adoption of new technologies. This study aims to analyze the impact of training and development, work motivation, and transformational leadership on employee competency. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that training and development, work motivation, and transformational leadership significantly influence employee competency. Notably, work motivation had the strongest impact on employee competency, with a T-statistic value of 6.94, followed by training and development, which was identified as a key factor in enhancing employee performance, with a T-statistic value of 5.62. Further research could explore additional variables such as rewards, work-life balance, and company values using alternative models and methodologies. This study provides insights to guide management in implementing effective policies to improve employee performance in alignment with company goals and available resources.